SOCIAL EDUCATION IN PANDEMIC COVID-19 IN STUDENT PERSPECTIVE - Bahagia; Leny Muniroh; Abdul Karim Halim; Rimun Wibowo; Nurussya’adah Sukiyah (al-Afkar, Journal For Islamic Studies, 2022)
The Covid-19 outbreak does not always have a negative impact. Every incident that God gives us, there is always wisdom tucked in it. This study aims to find various kinds of wisdom and social education from the Covid-19 Pandemic from the perspective of Semester 1 Students of the Faculty of Islamic Religion. Researchers use this type of qualitative research. with an ethnographic approach. Collecting data by observation, in-depth interviews, and documentation. Selection of informants with purposive sampling technique. Data analysis with data triangulation approach. The findings show that the wisdom of Covid-19 from the perspective of Semester 1 Students of the Faculty of Islamic Religion, Ibn Khaldun University, Bogor, can significantly increase social sensitivity. This is in the eyes of Islam as an implementation of Q.S. Al-Maidah verse 2. And social distancing as a tangible manifestation of Islamic law stated in Q.S. Al-Isra: 32. As well as an indication that Islam is a rukhsah religion in terms of congregational prayers